PCR-RFLP based method for molecular differentiation of sand fly species Phlebotomus argentipes, Phlebotomus papatasi and Sergentomyia babu found in India - Tiwary, Puja (2012)
PCR- Restriction fragment length polymorphism (RFLP) is a time saving and accurate technique to differentiate closely related organisms. In the regions endemic for visceral leishmaniasis (VL) in India, various species of morphological similar sand fly exists but only female Phlebotomus argentipes is the vector for VL. In the present study primers were designed targeting the 18S rRNA encoding gene that showed amplification in all the major sand fly species found in India. The amplified fragments were further digested using the Hinf I or Hpa II restriction enzymes. Each of the restriction enzyme produced species specific restriction patterns, which can easily be used to identify specific sand fly species. This technique can be employed in the identification of the species of the sand flies.